Ways of Being Together During the COVID-19 Pandemic: Support Bubbles and the Legal Construction of Relationships - Trotter, Sarah (Frontiers in Sociology, 2021)
This article focuses on the concept of the support bubble. The concept was introduced in New Zealand in March 2020 in the context of the COVID-19 pandemic to denote a network of people with whom a person could have physical contact, and was later taken up in various forms elsewhere, particularly in the UK. The article focuses on the meaning that was attached to the concept and to the ways of being together that it encapsulated and stipulated. Where support bubbles were formalised as a matter of law, as in New Zealand and the UK, a particular form of relating was legally constructed and real relationships were affected through law. The article addresses the meaning and implications of the concept of the support bubble in this light. First, it considers the concept of the support bubble as a new legal form, which drew in, and built on, a range of relationships and then recast them in terms of a new legal form. Second, it analyses the central question posed by the concept as one of the meaning of being together in a support bubble, not only for those navigating and living with the concept in practice, but also as mediated in and through law. Third, it outlines how the concept of the support bubble represented a distinct legal development. It enabled those who were eligible to define for themselves, albeit within a specified framework, the meaning and nature of a relationship of support of this kind. It also supplied a space in which some kinds of relationships that had not necessarily attracted much previous legal attention—like friendships and dating relationships—came to find a degree of legal reflection and recognition.